2003
DOI: 10.1207/s15327914nc4601_04
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of the Mediterranean Diet on Lung Cancer

Abstract: There has been growing interest over recent years in the potential preventive role of the Mediterranean diet in the development of cardiovascular disease and cancer. The present study was designed to evaluate the relationship between the components of the Mediterranean diet and lung cancer. A hospital-based, case-control study of lung cancer was conducted on subjects aged 35+ yr living in the Lazio region and admitted to one of the main hospitals in Rome in the period from 1993 to 1996. Cases (n = 342) were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 24 publications
5
66
0
2
Order By: Relevance
“…Furthermore, oleocanthal has also been shown to promote cell apoptosis by activating caspase-3 and poly-adenosine diphosphate-ribose polymerase, the phosphorylation of p53 (Ser15), and also induced fragmentation of DNA in HT-29 cells derived from human colon adenocarcinoma (Khanal et al, 2011). These findings suggest that oleocanthal may have potential as a therapeutic agent in the inhibition of carcinoma progression and supports substantial evidence that populations residing in the Mediterranean region have a reduced incidence of prostate, breast, lung and gastrointestinal cancer (Trichopoulou et al, 2000, La Vecchia, 2004, Fortes et al, 2003, Dixon et al, 2007. It is important to note that while there is strong evidence that oleocanthal is an effective antiinflammatory agent and demonstrates pharmacological characteristics in vitro, future in vivo studies are required to fully elucidate the efficacy of this natural NSAID.…”
Section: Oleocanthal and Cancersupporting
confidence: 68%
“…Furthermore, oleocanthal has also been shown to promote cell apoptosis by activating caspase-3 and poly-adenosine diphosphate-ribose polymerase, the phosphorylation of p53 (Ser15), and also induced fragmentation of DNA in HT-29 cells derived from human colon adenocarcinoma (Khanal et al, 2011). These findings suggest that oleocanthal may have potential as a therapeutic agent in the inhibition of carcinoma progression and supports substantial evidence that populations residing in the Mediterranean region have a reduced incidence of prostate, breast, lung and gastrointestinal cancer (Trichopoulou et al, 2000, La Vecchia, 2004, Fortes et al, 2003, Dixon et al, 2007. It is important to note that while there is strong evidence that oleocanthal is an effective antiinflammatory agent and demonstrates pharmacological characteristics in vitro, future in vivo studies are required to fully elucidate the efficacy of this natural NSAID.…”
Section: Oleocanthal and Cancersupporting
confidence: 68%
“…Epidemiologic studies have shown that olive oil markedly prevents the occurrence of several types of cancer but that it lacks therapeutic activity (Martin-Moreno, 2000;Stark and Madar, 2002;Fortes et al, 2003). Moreover, OA-rich oils have protective effects against tumor growth and metastasis in animal models (Kimura, 2002;Yamaki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of the Mediterranean diet against the development of cancer is well known; more specifically, high olive oil consumption is associated with a lower incidence of lung cancer (Fortes et al, 2003), breast cancer, and colon cancer (Stark and Madar, 2002). The main constituent of extra virgin olive oil is the triacylglycerol triolein, which contains three oleic acid (OA) molecules (70%-80% in olive oil).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that a diet rich in raw vegetables and olive oil protects against breast cancer [72]. Studies in Mediterranean countries revealed an inverse relation between consumption of olive oil and cancers of the bladder [23], stomach [21], urinary tract [24], and lung [22] [73].…”
Section: Oleaceaementioning
confidence: 99%